Some comments on the composition and analysis of onomastic units of Navoi region - Orolboy Oripov; Saboat Khudjanazarova (Genius Journals, 2022)
It is known that onomastics is a branch of linguistics that studies all nouns, and the history of their appearance and change. Extensive research on Uzbek onomology has enriched the field of Uzbek onomastics with a number of monographs, explanatory dictionaries, numerous scientific articles, candidate and doctoral theses. This article describes the development prospects of Uzbek language onomastics, including anthroponymics.
Keywords: anthroponyms; proper noun; toponymy; oikonyms